2020
DOI: 10.3889/oamjms.2020.4192
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Community Empowerment on Preventing Dengue Fever in Lampung Province, Indonesia

Abstract: AIM: The aim of this study was to determine the effects of community empowerment on preventing dengue fever in Lampung Province, Indonesia. METHODS: This study used a quasi-experimental design with two groups of pretest-posttest design. The number of samples in this study was 120 people in the intervention group and 120 people in the control group, who is a housewife living in Gading Rejo and Pringsewu subdistrict, Lampung, Indonesia. The sampling technique used a proportional stratified random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…The current research involved a quasi-experimental study of community empowerment. As our proposed model was shown to decrease the larval indices values, it concurred with the findings of a study exploring the role of water containers between two groups in Lampung Province, Indonesia [35]. We also observed that most community members showed high satisfaction with the model and that they required continued community projects and perceived that the LWIs of the 10 villages and 4 child development centers decreased the dengue outbreaks.…”
Section: Discussionsupporting
confidence: 86%
“…The current research involved a quasi-experimental study of community empowerment. As our proposed model was shown to decrease the larval indices values, it concurred with the findings of a study exploring the role of water containers between two groups in Lampung Province, Indonesia [35]. We also observed that most community members showed high satisfaction with the model and that they required continued community projects and perceived that the LWIs of the 10 villages and 4 child development centers decreased the dengue outbreaks.…”
Section: Discussionsupporting
confidence: 86%
“…This study's results indicate a significant relationship between community empowerment and the MHP activity (P value 0.001). The effect of community empowerment in increasing campaign capacity has successfully prevented dengue fever (Farich et al, 2020). Associated with this research is the prevention of Covid-19 transmission with MHP behavior.…”
Section: The Relationship Of Community Empowerment and Mhp Activitymentioning
confidence: 99%
“…The community needs to be equipped with knowledge about the program so that they can play an active role and determine the success of the program [33]. Education can also be provided directly to communities in dengue-endemic areas [34].…”
Section: Outcomementioning
confidence: 99%